1998
DOI: 10.3354/meps164199
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-limited growth of the coral reef macroalga Sargassum baccularia and experimental growth enhancement by nutrient addition in continuous flow culture

Abstract: ABSTRACT-The observed high biomass of Sargassum species and other fleshy macroalgae on nearshore coral reefs in the Great Barner Reef (Australia) raises the concern that this may be a sign of a phase shift from hard coral to dominance by algae, thus indicating the degradation of these reefs. Nearshore reefs are, due to their geographical position, exposed to inputs of nutnents and particles from mainland run-off. This study estimated the limiting and optimum nutrient concentrations for the growth of Sargassum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 23 publications
2
61
0
3
Order By: Relevance
“…Wheeler & Björn -säter 1992), and comparable to some seaweeds from coral reefs (e.g. Schaffelke & Klumpp 1998, Lapointe et al 2005, Tsai et al 2005. These ranges of tissue phosphorus values are smaller than the ranges in seawater phosphate concentrations (3.43-fold) and phosphate uptake rates at 5 μM, which varied from 2.88-fold in P. lucida to 10.94-fold in Melanthalia abscissa.…”
Section: Ulva Intestinalismentioning
confidence: 80%
See 1 more Smart Citation
“…Wheeler & Björn -säter 1992), and comparable to some seaweeds from coral reefs (e.g. Schaffelke & Klumpp 1998, Lapointe et al 2005, Tsai et al 2005. These ranges of tissue phosphorus values are smaller than the ranges in seawater phosphate concentrations (3.43-fold) and phosphate uptake rates at 5 μM, which varied from 2.88-fold in P. lucida to 10.94-fold in Melanthalia abscissa.…”
Section: Ulva Intestinalismentioning
confidence: 80%
“…Some brown seaweeds have very low K m values for phosphate uptake: Laminaria japonica (Ozaki et al 2001) and Sargassum baccularia (Schaffelke & Klumpp 1998) have K m values of 0.14 and 0.26 μM, respectively. However, red and green seaweeds in general have lower K m values for phosphate uptake (4 μM or less) than brown seaweeds (Rees 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown a rapid uptake response by tropical algae when they are exposed to short-duration pulses of enhanced nutrients in controlled experiments (Lapointe 1985;Schaffelke and Klumpp 1998a,b;Schaffelke 1999). After uptake, some species store excess nutrients, whereas others have limited storage capacity (e.g., Ulva spp.)…”
mentioning
confidence: 99%
“…Considering a 10:1 DW:FW ratio and average values of nitrogen (Pyropia/Porphyra: 5.5%, Gracilaria: 3.0%, Kappaphycus/Eucheuma: 1.7%, kelp: 2.0% and Sargassum: 4.1%) and carbon (Pyropia/Porphyra: 38%, Gracilaria: 28%, Kappaphycus/Eucheuma: 29%, kelp: 30% and Sargassum: 34%), the total nitrogen and carbon removal by these five major aquaculture groups is approximately 54 million t of nitrogen per year and 700 million t of carbon per year (equivalent to 2600 million t of CO 2 ), respectively (Asare and Harlin 1983;Gerard 1997;Schaffelke and Klumpp 1998;Gevaert et al 2001;Schaffelke 2001;Chung et al 2002;Rawson et al 2002;Sahoo and Ohno 2003;Dean and Hurd 2007;Kim et al 2007Kim et al , 2014aKim et al , 2015aBuschmann et al 2008;Abreu et al 2009;Robertson-Andersson et al 2009;Levine and Sahoo 2010;Broch et al 2013). This is, in fact, a significant amount of carbon and nitrogen removal.…”
Section: Ecosystem Servicesmentioning
confidence: 99%